Die wilden Hühner - Funke, Cornelia (Dressler, 2015)
Als Charlottes Oma verreist ist, gründen die 4
Keywords: Kinderbande; IND: s; Kinderbuch; Streit; IND: s; Clique; Gruppe; Verlieben; Weibliche Jugend; Lebensrettung; Huhn; Mädchen